2021
DOI: 10.3390/coatings11040442
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Gum Arabic and Starch-Based Edible Coatings with Lemongrass Oil Using Response Surface Methodology for Improving Postharvest Quality of Whole “Wonderful” Pomegranate Fruit

Abstract: The effects of edible coatings based on gum arabic (GA) (0.5–1.5%), maize starch (MS) (0.5–1.5%), lemongrass oil (LO) (2–4%), and glycerol (GC) (0.5–1%) developed using response surface methodology (RSM) on “Wonderful” pomegranate fruit were studied. After 42 days of storage (5 ± 1 °C, 95 ± 2% RH) and 5 days at ambient temperature (20 ± 0.2 °C and 60 ± 10% RH), whole fruit were evaluated for weight loss (%) and pomegranate juice (PJ) for total soluble solids (°Brix), titratable acidity (% Citric acid), and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 69 publications
0
26
0
Order By: Relevance
“…The coating solutions consisting of gum Arabic (0.5% w/v) (Sigma-Aldrich, Johannesburg, South Africa), maize starch (0.5% w/v) (Chem. lab suppliers Co., Johannesburg, South Africa), glycerol (1% v/v) (Sigma-Aldrich, Johannesburg, South Africa), tween 80 (0.05% v/v) (Sigma-Aldrich, Johannesburg, South Africa) and lemongrass oil (3% v/v) (Umuthi Botanicals, Wilderness, South Africa) were prepared in 1000 mL mill-Q water according to optimization procedure conducted by Kawhena et al [49]. The solutions were continuously stirred at low heat (25 • C) for 1 h on a hot plate magnetic stirrer (Spinot, Tarsons, New Delhi, India).…”
Section: Formulation Of Coating Solutionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The coating solutions consisting of gum Arabic (0.5% w/v) (Sigma-Aldrich, Johannesburg, South Africa), maize starch (0.5% w/v) (Chem. lab suppliers Co., Johannesburg, South Africa), glycerol (1% v/v) (Sigma-Aldrich, Johannesburg, South Africa), tween 80 (0.05% v/v) (Sigma-Aldrich, Johannesburg, South Africa) and lemongrass oil (3% v/v) (Umuthi Botanicals, Wilderness, South Africa) were prepared in 1000 mL mill-Q water according to optimization procedure conducted by Kawhena et al [49]. The solutions were continuously stirred at low heat (25 • C) for 1 h on a hot plate magnetic stirrer (Spinot, Tarsons, New Delhi, India).…”
Section: Formulation Of Coating Solutionsmentioning
confidence: 99%
“…All treatment combinations are summarized in Table 1. Weight loss was determined according to Kawhena et al [49] using an electronic weighing balance (ML3002.E, Mettler Toledo, Zurich, Switzerland). For each treatment combination, the weight of ten randomly selected fruit was continuously measured during storage, and weight loss was calculated using the following Equation (1):…”
Section: Packaging and Storagementioning
confidence: 99%
See 2 more Smart Citations
“…Lemon essential oil, used as a food additive or favouring agent, is extracted from Citrus lemon and its main components are limonene, valencene and ocimene [15]. Lemongrass essential oil is a natural mixture of different compounds such as terpenes, alcohols, aldehydes, ketones, carboxylic acids, and others found to exhibit antimicrobial activity against different types of microorganisms [16] and can be used as an active ingredient in edible coatings. Kapetanakou et al [17] observed the positive effect of using sodium alginate coatings incorporated with cinnamon essential oil (0.3% and 0.9% v/v) as a natural active compound on the fungal growth and ochratoxin A production in coated apple and pears.…”
Section: Introductionmentioning
confidence: 99%